Unlocking plant growth-promoting traits of endophytic actinobacteria isolated from Anacyclus pyrethrum, an endemic medicinal plant of the Aguelmam azegza region, Morocco - Aguennouz, Rachid; Aallam, Yassine; Haddioui, Abdelmajid; Hamdali, Hanane (Frontiers in Microbiology, 2025)
IntroductionThe present study reports, for the first time to our knowledge, the isolation and characterization of endophytic actinobacteria from the medicinal plant Anacyclus pyrethrum.MethodsA total of 100 endophytic actinobacterial strains were isolated from root tissues. Based on their distinct morphological characteristics observed on ISP2 and Bennett media, thirteen representative isolates were selected for further screening of their plant growth-promoting traits and antimicrobial activities. These isolates were evaluated for their ability to solubilize inorganic phosphate, produce Indole-3-Acetic Acid (IAA), and exhibit antibacterial and antifungal activities. Antibacterial assays targeted Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus, while antifungal activity was assessed against Fusarium fujikuroi.ResultsApproximately 80% of the selected isolates displayed plant growth-promoting potential under in vitro conditions. Five isolates (38.46%) tested positive for IAA production, with AGS05 and AGS08 producing the highest concentrations (87.54 μg/mL and 89.79 μg/mL, respectively). Moderate IAA production was observed in AGS13 (59.23 μg/mL) and AGS09 (35.31 μg/mL). Furthermore, nine isolates (69.23%) exhibited phosphate-solubilizing abilities, as evidenced by clear halo formations on Synthetic Minimum Medium (SMM) containing 0.5 g/L of tricalcium phosphate (TCP) or rock phosphate (RP) as the sole phosphorus sources. Quantitative assessment of phosphate solubilization in liquid SMM revealed that phosphate release increased significantly by day 7 across all tested strains. AGS08 released the highest amount of soluble phosphate from TCP (47.6 μg/mL, pH 3.55), followed by AGS03 (41.2 μg/mL, pH 3.85) and AGS13 (39.6 μg/mL, pH 3.75). Regarding RP solubilization, AGS10 exhibited the highest P release (7.8 μg/mL, pH 3.4), followed by AGS09 (7.0 μg/mL, pH 3.9) and AGS08 (6.4 μg/mL, pH 4.5). A consistent pH reduction was observed across all treatments, indicating microbial acidification during phosphate solubilization. Based on 16S rRNA gene sequencing and phylogenetic analysis, three isolates with multiple PGP traits were identified as Streptomyces species: S. albogriseolus [AGS8 (By8)] and S. variabilis [AGS5 (By5a) and AGS10 (By10)].DiscussionThese findings demonstrate that Anacyclus pyrethrum is a valuable reservoir of endophytic actinobacteria with remarkable plant growth-promoting and antimicrobial properties. The selected strains represent promising candidates for development as bioinoculants and biocontrol agents in sustainable agricultural systems.